If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 7(5 + -4x) = 63 (5 * 7 + -4x * 7) = 63 (35 + -28x) = 63 Solving 35 + -28x = 63 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-35' to each side of the equation. 35 + -35 + -28x = 63 + -35 Combine like terms: 35 + -35 = 0 0 + -28x = 63 + -35 -28x = 63 + -35 Combine like terms: 63 + -35 = 28 -28x = 28 Divide each side by '-28'. x = -1 Simplifying x = -1
| (2x^6)(6x^3)= | | 2-(x+4)=2x | | 2x^2+5x+7=5x+9 | | ln(90)-ln(6)-ln(3)= | | xy-7x-7y+49= | | Z=5x+2y | | k^3+8= | | 5m+10= | | 16+4x-4=x+12 | | a^2+15ab+54b^2= | | 5bc+2bc-4bc= | | 3-2x=-7 | | 4x+3y-2x+5y= | | k-4=k+5 | | 0.07x+0.05(1000-x)=65 | | 102-2x=34x+22 | | 8-9x=193-44x | | -2=4-x | | 0.05x=x-190 | | 5y=3y | | -13=x+1 | | 5=3x-9 | | 6-2x=-8 | | 6x+7=x+2 | | 13-9x=49-37x | | 6x+5=-19-8x | | y-5=18 | | 3(x+4)(x-3)=0 | | 8x-27=6x-5 | | 6p+3=8p+6 | | 35-3x=6x+21 | | 12-9x=76-23x |